Biocultural Restoration in Hawaiʻi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Biocultural restoration is a process by which the various connections between humanity and nature, as well as between People and Place are revived to restore the health and function of social-ecological systems. This collection explores the subject of biocultural restoration and does so within the context of Hawaiʻi, the most remote archipelago on the planet. The Hawaiian Renaissance, which started in the 1970s, has led to a revival of Hawaiian language, practices, philosophy, spirituality, knowledge systems, and systems of resource management. Many of the leading Indigenous and local scholars of Hawaiʻi who were born into the time of the Hawaiian Renaissance contributed to this collection. More than a third of the authors are of Indigenous Hawaiian ancestry; each paper had at least one Indigenous Hawaiian author, and several papers had a Hawaiian lead author, making this the largest collection to date of scientific publications authored by Indigenous Hawaiians (Kānaka ʻŌiwi). In addition, the majority of authors are women, and two of the papers had 100 percent authorship by women. This collection represents a new emphasis in applied participatory research that involves academics, government agencies, communities and both private and non-profit sectors.